The Effect of Smear Layer on the Push-out Bond Strength of Silicone-based Root Canal Sealer - Israa M. Attash; Wiaam M. O. AL-Ashou (University of Mosul, College of Dentistry, 2022)
Aims: The study aimed to evaluate the effect of smear layer on the push-out bond strength of silicone-based root canal sealers. Materials and methods: Sixty extracted, single-rooted, sound human mandibular first premolar teeth were selected for this study. The Crown portion of each tooth was decoronated to the level of cement-enamel junction to standardize the root length to 16 mm. The working length was measured by subtracting 1mm from the visually determined canal length and the canals were instrumented using ProTaper universal rotary system up to size F3. The canals were divided into two groups according to the irrigating solutions used. Group.1 was rinsed with 2.5% sodium hypochlorite followed by 17% EDTA to ensure complete smear layer removal. Group.2 was rinsed using 0.9% normal saline to keep the smear layer. Then the samples were subdivided into three subgroups according to the sealer used with gutta-percha. These include AH Plus, GuttaFlow 2, and GuttaFlow Bioseal groups. The push-out bond strength test was performed using the universal testing machine and the data were analyzed using independent sample T-test at (p ≤ 0.05) to compare the results of each sealer group in the presence and absence of the smear layer. Results: For all sealers' groups the results has shown a statistically significant difference in the bond strength at (p ≤ 0.05) between group 1 (without smear layer) and group 2 (with smear layer). The smear layer removal produced higher bond strength in AH Plus sealer, whereas the bond strength of both GuttaFlow 2 and GuttaFlow Bioseal was decreased when the smear layer was removed. Conclusion: Smear layer removal has a positive effect on the bond strength value of AH Plus sealer. The bond strength of GuttaFlow 2 and GuttaFlow Bioseal was not improved following smear layer removal.